Wildfire impacts on California spotted owl nesting habitat in the Sierra Nevada. Issue 11 (14th November 2016) - Stephens, Scott L.; Miller, Jay D.; Collins, Brandon M.; North, Malcolm P.; Keane, John J.; Roberts, Susan L.
Abstract: California spotted owls (CSOs) ( Strix occidentalis occidentalis ) have received significant conservation attention beginning with the U.S. Forest Service interim management guidelines in 1992. The most commonly reported forest habitat feature for successful nesting habitat of CSO is canopy cover > 70%. Loss and degradation of Sierra Nevada CSO habitat, however, has been a growing concern, initially from commercial tree harvesting and, more recently, from wildfire. This study examined trends in wildfire impacts on potential nesting habitat of the CSO and discusses different management approaches that might lead to the conservation of CSO in fire‐dependent forests. A total of 85, 046 ha of CSO potential nesting habitat was burned by fire that resulted in ≥ 50% tree basal area (BA) mortality, reducing canopy cover on average to < 25%, during 2000–2014; this included 2.7%, 12.3%, and 7.6% of dense red fir ( Abies magnifica ), eastside pine, and westside forests, respectively. Based on regression predictions, within the next 75 yr, the cumulative amount of nesting habitat burned at ≥ 50% tree basal area mortality will exceed the total existing habitat. Four management strategies are discussed that could enhance the conservation of the CSO: (1) increased fire suppression, (2) strategically reducing fire hazards using mechanical treatments and/or prescribed fire, (3) increasing the amount of managed wildfire in CSO habitat, and (4) developing a landscape strategy that uses historical forest structure information to identify areas where high‐canopy cover forests are more sustainable. Our estimates of how moderate‐ and high‐severity fire may affect forests into the future poise a substantial threat to CSO persistence. More comprehensive forest restoration activities may be needed in CSO habitat to avoid significant losses of older forests.